Identification and Characterization of a Neutral Locus for Knock-in Purposes in C. parapsilosis - Nemeth, Tibor; Papp, Csaba; Vagvolgyi, Csaba; Chakraborty, Tanmoy; Gacser, Attila (Frontiers in Microbiology, 2020)
Invasive fungal infections caused by Candida species affect approximately 700,000 people worldwide resulting in 300,000 deaths annually. Besides Candida albicans, other members of the genus have gained relevance in the last two decades, including C. parapsilosis whose incidence is particularly high amongst low birth weight neonates. To investigate the virulence properties of this pathogen several techniques have been developed for generating knock-out mutants; however, no target locus for knock-in approaches has been published so far. Here we report CpNEUT5L (N5L), an intergenic locus in C. parapsilosis, and introduce an integrative GatewayTM and a classical ligation based replacement plasmid to target it with. As a proof of principle, we fluorescently tagged laboratory and prototroph strains and established that this locus is also suitable for reintegration purposes. We concluded that GFP-expressing constructs integrated into this region provide strong, homogenous fluorescent signals while alteration of this locus affects neither the growth of the mutants in liquid or on solid media, even in the presence of different stressors, nor their basic virulence properties. Hence, our findings demonstrate that N5L is a highly effective neutral locus for knock-in approaches in C. parapsilosis.